PTU-212 To analyse the risk of stent migration with the Niti-S covered flared biliary stent. (28th May 2012) - Moore, J K; Davies, M; Sheridan, M
Abstract : Introduction: Stent migration occurs in 6%–12% of patients undergoing biliary stenting 1 The Niti-S fully covered metal stent (Taewoong Medical, Seoul) has a flared end which acts as anti-migration. 2 Few studies have evaluated the efficacy of these stents and are contradictory 3 4 The aim of our study is to compare their migration rates, investigate contributory factors and patient outcomes. Methods: This was a retrospective cohort study. 32 Niti-S flared stents were placed between January 2010 and July 2011. Each of the patients' records were analysed. The indication for stent, size and whether there had been any previous endoscopic therapy was recorded. The cholangiograms were then re-reviewed by an experienced radiologist to assess stricture length and position of the stent proximal to the stricture. Results: 10 out of 32 stents (31%) had migrated. Nine were placed for benign strictures and one for a malignant stricture. There was no significant difference between the stents that did and did not migrate comparing the length of stricture (mean 11.8 mm vs 12.4 mm), or where the stent was placed (mean proportion of stent above the proximal end of the stricture 16 mm vs 17.5 mm). There also appeared to be no association with previous endoscopic therapy: in 6 (60%) of the procedures where the stents had migrated there had been previous therapy, compared to 14 of the remaining 22 procedures (64%). 4 of the 9 (44%) patients with migrated stents were subsequently admitted to hospital with cholangitis, compared to 1 patient who did not have a migrated stent. Conclusion: The flared end covered metal stents significantly migrate despite the theories behind the design. Direct cost implications of this should be sought. There appears to be no association between aetiology, length of stricture, previous endoscopic therapy or where the stent was placed and subsequent migration. Competing interests: None declared. References: 1. Kullman E, Frozanpor F, Soderland C, et al. Covered versus uncovered self-expandable nitinol stents in the palliative treatment of malignant distal biliary obstruction: results from a randomised, multicenter study. Gastrointest Endosc 2010;72 :915–23. 2. Park do H, Song TJ, Eum J, et al. EUS—guided hepaticogastrostomy with a fully covered metal stent as the biliary diversion technique for an occluded biliary stent after a failed ERCP (with videos). Gastrointest Endosc 2010;71 :413–19. 3. Park do H, Lee SS, Lee TH, et al. Anchoring flap versus flared end, fully covered self-expandable metal stents to prevent migration in patients with benign biliary strictures: a multicentre, prospective, comparative pilot study (with videos). Gastrointest Endosc 2011;73 :64–70. 4. Han YM, Gin GY, Lee SO, et al. Flared polyurethane covered self-expandable Nitinol stent for malignant biliary obstruction. J Vasc Interv Radiol 2003;14 :1291–301.